Hedgehog Inhibitors in Rhabdomyosarcoma: A Comparison of Four Compounds and Responsiveness of Four Cell Lines - Ridzewski, Rosalie; Rettberg, Diana; Dittmann, Kai; Cuvelier, Nicole; Fulda, Simone; Hahn, Heidi (Frontiers in Oncology, 2015)
Rhabdomyosarcoma (RMS) are the most common soft tissue sarcoma in children and are divided into two major histological subgroups, i.e. embryonal (ERMS) and alveolar RMS (ARMS). RMS can show HEDGEHOG/SMOOTHENED (HH/SMO) signaling activity and several clinical trials using HH inhibitors for therapy of RMS have been launched. We here compared the antitumoral effects of the SMO inhibitors GDC-0449, LDE225, HhA and cyclopamine in two ERMS (RD, RUCH-2) and two ARMS (RMS-13, Rh41) cell lines. Our data show that the antitumoral effects of these SMO inhibitors are highly divers and do not necessarily correlate with inhibition of HH signaling. In addition, the responsiveness of the RMS cell lines to the drugs is highly heterogeneous. Whereas some SMO inhibitors (i.e. LDE225 and HhA) induce strong proapoptotic and antiproliferative effects in some RMS cell lines, others paradoxically induce cellular proliferation at certain concentrations (e.g. 10 µM GDC-0449 or 5 µM cyclopamine in RUCH-2 and Rh41 cells) or can increase HH signaling activity as judged by GLI1 expression (i.e. LDE225, HhA and cyclopamine). Similarly, some drugs (e.g. HhA) inhibit PI3K/AKT signaling or induce autophagy (e.g. LDE225) in some cell lines, whereas others cannot (e.g. GDC-0449). In addition, the effects of SMO inhibitors are concentration-dependent (e.g. 1 µM and 10 µM GDC-0449 decrease GLI1 expression in RD cells whereas 30 µM GDC-0449 does not). Together these data show that some SMO inhibitors can induce strong antitumoral effects in some, but not all, RMS cell lines. Due to the highly heterogeneous response we propose to conduct thorough pretesting of SMO inhibitors in patient-derived short term RMS cultures or patient-derived xenograft mouse models before applying these drugs to RMS patients.